Perendaman semen ionomer kaca konvensional dalam kefir terhadap kekerasan permukaan - Soraya Dian Permata Rezky; Titien Hary Agustantina; Devi Rianti (DiscoverSys Inc., 2010)
Conventional glass ionomer cement is a restorative material used in dentistry. Kefir isa beverage as a result of milk fermentation milk and kefir seeds. Know the change ofsurface hardness in conventional glass ionomer cement after soaking in kefir. Ninesample discs (5 mm in diameter and 3 mm thick)were prepared, each disc contained 6samples. All samples prepared following the manufacturers’ instructions then kept for24 hours at room temperature before soaking in aquades and kefir. Vickersmicrohardness was used to measure the surface hardness at the top surface of thesample. Data were statistically analyzed using ANOVA and LSD (p < 0.05). This studyindicated that soaking of conventional glass ionomer cement in aquades and kefirdecreased surface hardness. The conclusion is conventional glass ionomer cementsoaked in kefir for a long time (108 hours) decreased in the surface hardness largely.